Reading development and the teaching of reading : a psychological perspective - Oakhill, Jane; Beard, Roger (Blackwell, 1999)
The new literacy. How research might inform the debate about early reading acquisition. Cognitive research and the misconceptions of reading education. Constructing meaning: the role of decoding. Phases of development in learning to read words. Learning to read words turns listeners into readers. Dyslexia. Meaninglessness, productivity and reading. Phonological development and reading by analogy. The messenger may be wrong, but the message may be right. Afterword.